The international thought of Martin Wight - Hall, Ian 1975- (Palgrave Macmillan history of international thought series, 2006)
Martin Wight's international thought inspired a generation of students at the London School of Economics and continues to animate the so-called "English school" of international relations. This new study, drawing upon his published writings and unpublished papers, examines his work on international relations in the light of his wider thought, his religious beliefs, and his understanding of history.